Experimental Study on Time-Dependent Changes in Rheological Properties and Flow Rate of 3D Concrete Printing Materials - Hojae Lee (MDPI AG, 2021)
Three-dimensional concrete printing (3DCP) materials require a relatively low water-to-binder ratio (W/B) of 0.3 or less to ensure their buildability and flow properties are sufficiently maintained after mixing. In this study, the rheological properties of 3DCP materials with W/B 0.28 were evaluated up to 60 min after mixing, and the yield stress and plastic viscosity were analyzed over time. A gradual decrease in flow rate with time was observed during the transport of 200 kg of material per batch through a 20 m hose. To examine the time-dependent changes in flow rate and layer volume, a 2200 mm × 1000 mm test specimen was printed. The dependence of the layer width over time during the printing process was measured and analyzed. The experimental analyses showed that the flow rate and layer volume of the 3DCP material gradually decreased with time after mixing, which was correlated with the rheological properties.